Significantly improved outcomes – both in retention and CGI scores - using Long Acting Buprenorphine (LAB-Buvidal) versus treatment as usual for Opioid Dependence in Wales during the Pandemic - J. Melichar; L. Pearson; E. Richards; A. Lindsay; R. Greenwood (European Psychiatry, 2022)
Introduction We have been using LAB (Buvidal) in Cardiff after its pandemic use was funded by Welsh Government.